Produtos fitossanitários no controle de fungos fitopatogênicos em sementes de soja - Siega, Thayllane de Campos (2021)
The health condition of the seeds is a primary factor, since they are vehicles of phytopathogenic agents, which cause the reduction of their germination and vigor. In addition, when associated with seeds, these agents can originate primary foci of diseases in exempt areas. A significant number of diseases of economic importance that occur in soybeans are caused by pathogens transmitted by seeds. Thus, carrying out the treatment of soybean seeds with fungicides is one of the most effective practices in the control of seed and soil fungi, representing a low total cost of crop production. The goal of this work was to study the specific activity of fungicides in relation to phytopathogenic fungi, in the sanitary treatment of soybean seeds. The experiments were conducted in the Didactic Seed Analysis Laboratory and in the Plant Health Laboratory, located on the Dois Vizinhos campus of the Federal Technological University of Paraná. After characterizing the seed lot (one thousand seeds weight, water content, germination, vigor and Blotter Test), three studies were carried out: (1) Minimum inhibitory concentration (MIC), evaluation by the circle method, mycelial growth and inoculation of pathogens in the treated seeds; (2) Evaluation of germination, vigor, seedling length, dry matter mass, seedling field emergence, emergence speed index and average emergence time; (3) Greenhouse (incidence of pathogens, final emergence, length of area and root length). The results demonstrate that the MIC varies according to the pathogen studied, including, in some situations, differing from the concentration indicated by the manufacturers themselves. In vitro studies expose as much as possible the pathogens to the action of the active ingredients, however, the high toxicity in vitro is not always proven in a greenhouse, where several factors interfere with this exposure. The field emergence was not affected by the treatments in the commercial dose and treatment 4 (Micronutrient + (Imidacloprid + Tiodicarb) + (Carbendazim + Tiram) + Polymer) reduces the germination and vigor of the seeds.